Wet Friction of Rubbers Containing DAE or TDAE Process Oil in ESBR and ESBR/BR Blends. Issue 1 (19th June 2022) - Abbasi Shahdehi, Iman; Alimardani, Mohammad; Roshanaei, Hossein
Abstract: The inevitable need to replace conventional high aromatic process oils with new safe ones has made it critically important to investigate the extent of tire wet grip modification by process oils' aromatic content. Here, direct measurement of wet friction is conducted on emulsion styrene butadiene rubber (ESBR) and ESBR/butadiene rubber (BR) rubber blends containing either safe treated distillate aromatic extract (TDAE) or the conventional distillate aromatic extract (DAE) oils. Interestingly, the results reveal that the wet coefficient of friction for rubbers with TDAE is comparable or even better than rubbers with the DAE. This stands in contrast with previous predictions founded on indirect methods such as the values of loss factor tan δ at 0°C. Analysis of temperature dependent dynamic properties exhibits similar values of tan δ at 0°C for two oil types; however, a higher level of loss tangent for TDAE is found near the glass transition temperature. It is hypothesized that the frequency of loading imposed by the microtexture of the concrete counterface may have dictated the temperature range in which the TDAE can surpass the DAE in terms of the wet grip performance. The difference in the wet grip of rubbers having two oils is more pronounced for the ESBR/BR blend system.